2018
DOI: 10.11604/pamj.2018.29.137.12992
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone status in Ghanaian patients with chronic kidney disease

Abstract: IntroductionThere is limited data on the prevalence of thyroid dysfunction in Ghanaian individuals with chronic kidney disease (CKD). Studies exploring the effect of thyroid hormones on renal function decline are also scanty. Unrecognized thyroid dysfunction in CKD may increase the burden of adverse health outcomes. The aim of this study was to determine thyroid hormone status and lipid profiles in patients with CKD attending the Renal Unit of the Korle-Bu Teaching Hospital.Methods60 clinically euthyroid patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…In the present study, 25/45 (55.5%) patients were female and 20/45 (20%) were male and the obtained results were in contrast with the study by Petimani and Adake that 77.7% of patients (35/45) were male and 22.2% of them (10/45) were female [ 45 ]. These results were in agreement with the study by Rashead and Aryee et al [ 46 , 47 ]. Low thyroid hormone levels (i.e., triiodothyronine) have been associated with adverse cardiovascular sequela in CKD and kidney failure, but these metrics are confounded by malnutrition, inflammation, and comorbid states and hence may signify nonthyroidal illness (i.e., thyroid functional test derangements associated with underlying ill health in the absence of thyroid pathology).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, 25/45 (55.5%) patients were female and 20/45 (20%) were male and the obtained results were in contrast with the study by Petimani and Adake that 77.7% of patients (35/45) were male and 22.2% of them (10/45) were female [ 45 ]. These results were in agreement with the study by Rashead and Aryee et al [ 46 , 47 ]. Low thyroid hormone levels (i.e., triiodothyronine) have been associated with adverse cardiovascular sequela in CKD and kidney failure, but these metrics are confounded by malnutrition, inflammation, and comorbid states and hence may signify nonthyroidal illness (i.e., thyroid functional test derangements associated with underlying ill health in the absence of thyroid pathology).…”
Section: Discussionsupporting
confidence: 94%
“…In chronic renal disease, there is significant reduction in kidney function accompanied by iodine retention, metabolic acidosis and alteration of thyroid function [ 13 ]. There are a number of observational studies that have reported various modifications of thyroid function test profile in chronic kidney disease patients [ 14 , 15 ]. Thyroid dysfunction ensues in chronic kidney disease with a significant decrease in total and free T4, total and free T3 and elevated TSH that is associated with increasing renal impairment and reduced GFR [ 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was 1.7% of primary hyperthyroidism in patients with hyperglycaemia (MH and SH) and none among the good glycaemic controls. A similar study in Ghana by Tagoe et al 26 estimated 10.1% thyroid dysfunction in patients with hyperglycaemia and 5.1% among the good glycaemic controls. In a related study by Rai et al and Udiong et al 5,38 prevalence of thyroid dysfunction was found to be 46.5% among Nigerian diabetic patients.…”
Section: Discussionmentioning
confidence: 73%